PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI TOKO INFORMA AHMAD YANI BEKASI - Nabila Nabila; Jaenudin Jaenudin (SMART Management Journal, 2023)
This study aims to analyze the effect of service quality which consists of reliability, assurance, tangibles, empathy, and responsiveness to customer satisfaction at Informa Store, at Ahmad Yani - Bekasi. The research method used is descriptive quantitative. The author collected data in the form of a questionnaire, with a total of 110 respondents using Slovin to determine the sample size. The analytical methods used are descriptive statistical tests, validity tests, data reliability tests, normality tests, heteroscedasticity tests, correlation coefficients, coefficients of determination, simple linear regression tests, and hypothesis tests which are processed using the Statistical Package for Social Sciences (SPSS) version 25 program. Simultaneous test results show that the quality of service (X) which consists of reliability, assurance, physical evidence (tangibles), empathy (empathy), and responsiveness (responsiveness) have a significant effect simultaneously (together). the same) on the customer satisfaction variable with a significance value (P value) of 0.003